Aplikasi Steganografi Berbasis Android Menggunakan End of File dengan Enkripsi Rivest Code 4 : Android-Based Steganography Application Using End of File with Rivest Code 4 Encryption - Achmad Aditya Ashadul (KRESNA: Jurnal Riset dan Pengabdian Masyarakat, 2022)
The research aim is to hide audio files through video media using the EOF (End of File) method and Rivest Code 4 encryption. The EOF (End of File) method is used as a message-hiding technique in steganography by inserting a message at the end of the container media file. Audio files are encrypted using Rivest Code 4 (RC4) and inserted at the end of the video file as container media. The results of this study are android-based steganography applications that can maintain the confidentiality of audio files while maintaining the quality of video files as container media.